Improving Appropriate Use of Omega-3 Fatty Acids for Patients With Dyslipidemia: Effect of Online CME. Issue 4 (December 2021) - Spyropoulos, Jelena; Boutsalis, George; Lucero, Katie; Waskelo, Joyce; Wilson, Kanetha; Anderson, David R.
Abstract : Hypertriglyceridemia is associated with an increased risk of atherosclerotic cardiovascular (CV) disease. Clinical trials have demonstrated the effectiveness of eicosapentaenoic acid ethyl ester (EPA), an omega-3 polyunsaturated fatty acid, on triglyceride lowering and on CV risk reduction. However, many clinicians have limited understanding of the effects of EPA and limited experience using EPA to reduce the risk of CV disease. An analysis was conducted to determine whether an online continuing medical education (CME) intervention could improve knowledge and competence of primary care physicians (PCPs) and cardiologists related to the role of EPA in management of CV risk in patients with dyslipidemia. The intervention comprised 2 online video-based CME activities. The effects of education were assessed for learners who completed 4 pre- and postassessment questions for each activity, using a matched pre-/postassessment design. For all questions combined, a McNemar's χ 2 test assessed differences from pre- to postassessment. Matched-learner data indicated that 34% of PCPs improved their knowledge as a result of participating in the activities, and 42% had their knowledge reinforced. Among cardiologists, 28% improved their knowledge, and 61% had their knowledge reinforced. For these learner subsets, there was a significant 17% relative increase in self-assessed confidence in appropriate use of EPA for PCPs (n = 1644, P < 0.001) and a 12% increase for cardiologists (n = 524; P < 0.001). The improvements observed in this online CME intervention demonstrate the benefits of educating the appropriate target audience base and suggest that this type of intervention can translate into improvements in clinical care.